2017
DOI: 10.1177/0884533617697936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self‐Reported Distress Thermometer Score on the Maximal Handgrip and Pinch Strength Measurements in Hemodialysis Patients

Abstract: Paradoxically higher self-reported DT scores were associated with younger age and lean body mass. As such, younger healthier, rather than more comorbid, patients may have greater expectations for their health and therefore report more distress. We found no association between DT scores and HGS, and as such, although HGS is a voluntary test, it appears to be a robust test independent of patient stresses. However, PS was lower in patients with higher DT scores, and as such, greater care may be required in interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Although relying on patient participation requiring a measurement of maximum voluntary muscle strength, HGS has been shown to be a reliable reproducible test to detect muscle weakness that can be readily performed in the clinic and on the dialysis unit . Previous reports have shown that HGS is a robust test of muscle strength that is not affected by patient self‐reported distress . Although there is no consensus definition for sarcopenia, speciality interest groups in both North America and Europe recommend measuring HGS in diagnosing sarcopenia …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although relying on patient participation requiring a measurement of maximum voluntary muscle strength, HGS has been shown to be a reliable reproducible test to detect muscle weakness that can be readily performed in the clinic and on the dialysis unit . Previous reports have shown that HGS is a robust test of muscle strength that is not affected by patient self‐reported distress . Although there is no consensus definition for sarcopenia, speciality interest groups in both North America and Europe recommend measuring HGS in diagnosing sarcopenia …”
Section: Discussionmentioning
confidence: 99%
“…13,25 Previous reports have shown that HGS is a robust test of muscle strength that is not affected by patient self-reported distress. 12 Although there is no consensus definition for sarcopenia, speciality interest groups in both North America and Europe recommend measuring HGS in diagnosing sarcopenia. 3,4 We measured HGS in a large, multiethnic dialysis population attending for outpatient dialysis treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Prescribed medications were reviewed from the hospital patient electronic records. 22 21 Our HD population is multi-ethnic, with English a second language for many patients, so to overcome language and literacy difficulties, we chose the visual distress thermometer, rather than written questionnaires to record self-reported psychological well-being.…”
Section: Methodsmentioning
confidence: 99%